Freshwater as a global commons: international governance and the role of Germany. - Herrfahrdt-Pähle, Elke; Scheumann, Waltina; Houdret, Annabelle; Dombrowsky, Ines (My University, 2019)
This study reveals that the current global water governance architecture is a highly fragmented and incoherent regime consisting of numerous norms, paradigms and actors, each covering single aspects of global water governance. Given the diversity of issues, a “classical” formation of one comprehensive international water regime in the form of a framework convention, and equipped with a specific global governance institution (such as for climate stability, biological diversity or the prevention of desertification) has so far not emerged. The authors suggest a global water governance regime that could evolve from the improved interplay of the existing elements of global water governance (i.e. norms, targets, paradigms and actors). This could be complemented by two innovations at UN level: installing an Intergovernmental Body on Water allowing for mandated decisions on water in the UN system, and a Scientific and Practice Panel on Water improving the science-policy interface. Such an approach that combines global norms and joint guidelines to be adapted to local contexts and needs may be able to increase urgently needed political support for governing water as a global commons, beyond the nation-state interests and their perception of water resources as sovereign goods.
Keywords: Trinkwasser; Trinkwasserbedarf; Zugänglichkeit; Wasserressourcen; Wasserreserve; Flussgebietsmanagement; Desertifikation; Integrierter Umweltschutz; Internationale Zusammenarbeit; Entwicklungspolitik; Global Commons; Global Governance